Contemplative Qualitative Inquiry: A Review - Guthrie, Kate (Qualitative report, 2020)
The following is a review of the book Contemplative Qualitative Inquiry: Practicing the Zen of Research by Valerie J. Janesick and published in 2015. This review aims to highlight the book’s unique features, primarily focusing on the ways in which Janesick appropriately weaves essential aspects of qualitative research and Zen alongside one another. Janesick offers readers, novice or experienced researchers, a unique way of understanding and approaching the practice of qualitative inquiry. The review highlights features of each chapter and concludes with how instructors of qualitative research methods may benefit from Janesick’s many suggestions for pedagogy and practice.